Oleanolic Acid and Ursolic Acid Induce UGT1A1 Expression in HepG2 Cells by Activating PXR Rather Than CAR - Yao, Na; Zeng, Caiwen; Zhan, Tao; He, Fang; Liu, Mingyi; Liu, Fanglan; Zhang, Hong; Xiong, Yuqing; Xia, Chunhua (Frontiers in Pharmacology, 2019)
Background: Oleanolic acid (OA) and its isomer ursolic acid (UA) have recently emerged as research foci based on their biologic activities. We previously demonstrated that UA can inhibit the activities of UGT1A3 and UGT1A4, and OA inhibits UGT1A3 activity in liver microsomes. However, whether OA and UA affect the expression of UGT1As in HepG2 cells and the underlying regulatory mechanism remain unclear. Purpose: The present study aimed to explore the effect of OA and UA on the expression of UGT1As in HepG2 cells and the regulatory mechanisms on UGT1A1 based on the pregnane X receptor (PXR) and constitutive androstane receptor (CAR) signaling pathways. Methods: We analyzed the effect of OA and UA on UGT1A expression and on the PXR/CAR regulatory pathway in HepG2 cells, hPXR-silenced HepG2 cells, and hCAR-silenced HepG2 cells by Q-PCR, Western blotting, and dual-luciferase reporter gene assays. Results: In HepG2 cells, OA and UA both significantly induced the expression of UGT1A1, UGT1A3, UGT1A4, and UGT1A9 and upregulated the expression of PXR. However, OA and UA did not affect CAR expression. A dual-luciferase reporter assay showed that OA and UA could markedly promote PXR-mediated UGT1A1 luciferase activity, whereas OA and UA did not affect CAR-mediated UGT1A1 luciferase activity. In hPXR-silenced HepG2 cells, OA and UA did not elevate UGT1A1 activity compared to the control group. However, the expression of UGT1A1 in hCAR-silenced HepG2 cells was markedly elevated compared to the control group or with non-silenced HepG2 cells treated with OA (10, 20, and 40 μM) or UA (10, 20, and 40 μM). Conclusions: OA and UA significantly induce the expression of UGT1A1, UGT1A3, UGT1A4, and UGT1A9 in HepG2 cells, and their induction on UGT1A1 is mediated by PXR activation, not CAR.